Pregnant women's preparation and perceptions about mode of delivery - Cleidiane Lopes dos Santos; Cleunir de Fátima Candido de Bortoli; Lisie Alende Prates; Kelly Bernardi Guimarães; Gisele Iopp Massafera; Priscila Bisognin (Universidade Federal de Santa Maria, 2016)
Aim: to know the preparation and perceptions of pregnant women about mode of delivery. Method: descriptive, qualitative research, developed with eight pregnant women, in September 2014, in a municipality in the southwest region of the State of Paraná. The data were collected through semi-structured interview and analyzed by thematic content analysis technique of operative proposal. Results: the vaginal birth has emerged as the participants' preferred manner of delivery. The preparation for childbirth took place, especially, during the prenatal period, being the doctor the professional who was mostly involved in the guidelines, but also the one that most influenced the decision concerning the mode of delivery. Conclusion: although the participants have revealed a preference for vaginal birth, because of impositions and lack of knowledge, at prenatal preparation they were convinced to perform the caesarean